Antimicrobial effects of silver nanoparticles and extracts of Syzygium cumini flowers and seeds: Periodontal, cariogenic and opportunistic pathogens - Carvalho Bernardo, Wagner Luis de [UNESP]; Gomes Boriollo, Marcelo Fabiano; Tonon, Caroline Coradi [UNESP]; Silva, Jeferson Junior da; Cruz, Fernando Moraes; Martins, Adriano Luis; Hofling, Jose Francisco; Palomari Spolidorio, Denise Madalena [UNESP] (Elsevier B.V., 2021)
Objective: This study aimed to analyze the antimicrobial effects of lyophilized hydroalcoholic extract (HEScSeed and HEScFlower) and silver nanoparticles (AgNPs-HEScSeed and AgNPs-HEScFlower) of S. cumini seed and flower, and to characterize some compounds of these extracts and their NPs. Design: Phytochemical screening was performed by GC-MS. Nanoparticles were characterized by UV-vis spectroscopy, energy-dispersive X-ray (EDX) spectrophotometry, scanning electron microscopy (SEM) and field emission gun (FEG), dynamic light scattering (DLS) and zeta potential (ZP). Antimicrobial susceptibility tests were analyzed by broth microdilution and agar diffusion methods. Results: HEScSeed and HEScFlower showed 7 and 17 phytochemical compounds, respectively. AgNPs-plant extracts were reported as stable and with variable shapes and sizes. All studied species (A. naeslundii, C. albicans, F. nucleatum, S. aureus, S. epidermidis, S. mutans, S. oralis and V. dispar) were susceptible to extracts and AgNPs-plant extracts, with varying degrees of antimicrobial activities (extract: 648.4-5,187.5 mu g/mL; AgNPs-plant: 31.2-2,000 mu g/mL). Conclusion: The extracts of S. cumini seed and flower have antimicrobial action against pathogens of medical and dental interest, whose MIC and MMC are species-dependent. The AgNPs-HEScSeed and AgNPs-HEScFlower have different shapes, sizes, organic compounds, stability and electronegativity (capping), characteristics that contribute to their bacteriostatic and fungistatic effects, but at significantly lower concentrations than plant extracts.
Keywords: Antimicrobial bioactivity; GC-MS; Green synthesis; Medical and oral pathogens; Plant extract